2006
DOI: 10.1093/europace/eul037
|View full text |Cite
|
Sign up to set email alerts
|

Pacing site and bradycardia dependent retrograde conduction block over an atrioventricular accessory pathway

Abstract: Intermittent retrograde conduction over an accessory pathway (AP) is an uncommon phenomenon. We report a case of Wolff-Parkinson-White syndrome in which retrograde conduction of the bypass tract was present only during right ventricular (RV) outflow tract and left ventricular pacing or during RV inflow tract pacing with a fast pacing rate (pacing site and bradycardia dependent conduction block). The interaction between different branches/fibres of the bypass tract might explain the mechanism of this phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Multiple cases have been reported with PMT but only some, like the present 10–12 . In this case, the patient received a dual‐chamber pacemaker after ablation of the atrioventricular node and in the electrophysiologic study, a left lateral accessory pathway was found.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Multiple cases have been reported with PMT but only some, like the present 10–12 . In this case, the patient received a dual‐chamber pacemaker after ablation of the atrioventricular node and in the electrophysiologic study, a left lateral accessory pathway was found.…”
Section: Discussionmentioning
confidence: 66%
“…Multiple cases have been reported with PMT but only some, like the present. [10][11][12] In this case, the patient received a dual-chamber pacemaker after ablation of the atrioventricular node and in the electrophysiologic study, a left lateral accessory pathway was found. During the tachycardia, the left lateral accessory pathway was the retrograde limb and not the atrioventricular node.…”
Section: Discussionmentioning
confidence: 83%
“…Bradycardia dependent block of retrograde conduction over the concealed accessory pathway is very rare with few isolated cases reported. [1][2][3] Differently, due to the absence of antegrade ventricular pre-excitation and arrhythmias recorded by ECG, it is difficult to make right diagnosis. Super normal conduction over AP might be an reasoned explanation in our case, usually characterized by a 'conduct-block-conduct' pattern of retrograde atrial activation during decremental ventricular pacing.…”
Section: Discussionmentioning
confidence: 99%